Understanding men’s psychological reactions and experience following a cardiac event: a qualitative study from the MindTheHeart project - Jalila Jbilou; Jean Grenier; Marie-Helene Chomienne; France Talbot; Heather Tulloch; Bianca D'Antono; Paul Greenman (BMJ Open)
Objectives Emotional issues such as depression, anxiety and post-traumatic stress disorder are common following a cardiac event. Despite their high prevalence, they often go undiagnosed and research suggests that men in particular are at higher risk. Therefore, a better understanding of men’s experiences with a cardiac event and ensuing health services is key for adapting approaches that meet their needs. The aim of this study was to describe the self-reported emotional challenges that men face following a cardiac event and to understand their patterns of psychosocial adjustment.Design Qualitative study (focus groups and one-on-one interviews) using an interpretive phenomenal analysis.Setting Clinical settings (cardiac departments in hospitals, cardiac rehabilitation programme and family medicine clinics) and in the community in three Canadian provinces.Participants A total of 93 men participated in the study through 22 focus groups and 5 semi-structured interviews, none has been excluded based on comorbidities.Results Four major themes emerged: (1) managing uncertainty and adversity; (2) distancing, normalising and accepting; (3) conformity to traditional masculine norms and (4) social, literacy and communication challenges.Conclusions Healthcare professionals caring for men following a cardiac event must be aware of the psychological and social adjustments that accompany the physical challenges. However, there is a lack of explicit guidelines, tools and clinical training in men-sensitive approaches. Further research is required to better inform clinical practices and healthcare services.